Implikasi Revolution in Military Affairs pada Perang Rusia-Ukraina 2022 terkait Kepentingan Geopolitik Keamanan Regional Amerika Serikat - Hidayat, Rizal Adhitya; Bustomi, Adonis Ghazi (Universitas Al-azhar Indonesia, 2024)
The development of technology in the military domain, such as data, artificial intelligence (AI), autonomy, space capabilities, hypersonic weapons, quantum, biotechnology, and New Material and Manufacture (NMM), has brought crucial changes to the dynamics of warfare. Major countries, including the United States (US), have adopted much of this technology, such as the advanced Ghost drone system with AI algorithms and the use of robotics at Tyndall Air Force Base and the US/Mexico border. In 2022, the US intervened in the Russia-Ukraine war as a decisive response to threats to national security. This intervention involved financial and military assistance, as well as the supply of weaponry like HIMARS and Phoenix UAS. The US also leveraged its defense alliances, particularly NATO, to bolster Ukraine and maintain national security interests, especially by strengthening positions in the Black Sea. Concerning the American Revolution in Military Affairs (RMA), which includes precision weapons, stealth technology, and C4ISR/information, Ukraine, in facing the war, adopted military technology supplied by the US. Thus, with these technological advancements, the shift in US military doctrine, particularly Multi-Domain Operations, became a guiding principle in supporting Ukraine. Additionally, the US underwent organizational changes in response to adapting to advanced technology. All of these aspects reflect the importance of adapting to technological changes in military strategy and organization.Keywords: Russia-Ukraine 2022, Geopolitics, Black Sea, RMA, Technology